2020
DOI: 10.1016/j.jaccas.2020.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Septal Rupture in 2 Patients Presenting Late after Myocardial Infarction during the COVID-19 Pandemic

Abstract: Ventricular septal rupture (VSR) following myocardial infarction is rare in the reperfusion era. The decrease in patients presenting with myocardial infarction during the coronavirus-2019 (COVID-19) pandemic could result in more frequent VSR. This report describes two patients with VSR presenting late after myocardial infarction and treated at a single institution. ( Level of Difficulty: Beginner. )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Beyond reduction in incidence, delayed presentations have been more common during the first wave, 25,26 with increases in overall symptom-to-hospital delays 24,27 along with increased out of hospital cardiac arrest rates, 11 and anecdotal evidence of increased delayed presentations and mechanical complications. [16][17][18][19][20] However, the incidence of cardiogenic shock has not increased in a large Danish registry. 28 In one Canadian study, the incidence of STEMI admission was not reduced during the pandemic period in Montreal, but unstable STEMI presentations and worse in-hospital course was more frequent, 29 data that we could not replicate with a much larger and broader sample size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond reduction in incidence, delayed presentations have been more common during the first wave, 25,26 with increases in overall symptom-to-hospital delays 24,27 along with increased out of hospital cardiac arrest rates, 11 and anecdotal evidence of increased delayed presentations and mechanical complications. [16][17][18][19][20] However, the incidence of cardiogenic shock has not increased in a large Danish registry. 28 In one Canadian study, the incidence of STEMI admission was not reduced during the pandemic period in Montreal, but unstable STEMI presentations and worse in-hospital course was more frequent, 29 data that we could not replicate with a much larger and broader sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Anecdotal evidence supports increased delayed or late presentations leading to increased mechanical complications. [16][17][18][19][20] The first wave of the COVID-19 pandemic has not occurred homogeneously throughout Canada. While the province of British Columbia (BC) was affected first, Quebec and Ontario experienced the greatest infection burden during the first wave of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical complications following delayed MI presentations were described in a total of 26 case reports only (level of clinical evidence: IV) in 21 selected articles included in this study, dating from June 2020 to May 2021. 7 - 27 No gender predominance was noted as the male-to-female ratio was 1:1). The age of patients ranged from 37 to 87 years (mean ± standard deviation = 64.12 ± 53.70 years).…”
Section: Resultsmentioning
confidence: 97%
“…The data regarding patient demographics, presenting symptoms, time from symptom onset to presentation, electrocardiographic features, anatomic findings, nature of mechanical complications, left ventricular ejection fraction, treatment, and clinical outcomes are summarized ( Table 3 ). 7 - 27…”
Section: Resultsmentioning
confidence: 99%
“…1 Parikh et al reported two patients with late presenting AMI complicated by VSR. 4 One patient expired due to multi-organ failure despite mechanical circulatory support. Second patient underwent surgical repair after a failed percutaneous VSR closure.…”
Section: Introductionmentioning
confidence: 99%